(3OjhGf GdUQUQjs - (3jMji Hf jhSa Hf jMji GdCfUGQj, GdUQUQj, LeGd GdOjf CHh RcQjG,J (B656 (3g` s
(3ChdgG (B:s
(3bGd GHhRcQjG jPcQ ajgG efGRd GdYTQI QVhGf Gddg Ydjge Sbi GdoYPrjH ef GdCehGg eG YPHG hgR faM GdUHG ef HGfg GdYPHG s
(3BNQgG (B:s
(3hCYXe GdfaY efg aj GdeYGOdgG EPG SbGgG pQhG YPHG aQhGgG s
(3GfXQ GdLRA GdChd HQbe (B321 (3COHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B236 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B523s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B141 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B797s
Keywords: (3GdCOHs